Complete mitochondrial DNA sequences of the Victoria tilapia (Oreochromis variabilis) and Redbelly Tilapia (Tilapia zilli): genome characterization and phylogeny analysis - Kinaro, Zachary Omambia; Xue, Liangyi; Volatiana, Josies Ancella (My University, 2015)
The Cichlid fishes have played an important role in evolutionary biology, population studies and aquaculture industry with East African species representing a model suited for studying adaptive radiation and speciation for cichlid genome projects in which closely related genomes are fast emerging presenting questions on phenotype–genotype relations. The complete mitochondrial genomes presented here are for two closely related but eco-morphologically distinct Lake Victoria basin cichlids, Oreochromis variabilis, an endangered native species and Tilapia zilli, an invasive species, both of which are important economic fishes in local areas. The complete mitochondrial genomes determined for O. variabilis and T. zilli are 16 626 and 16,619 bp, respectively. Both the mitogenomes contain 13 protein-coding genes, 22 tRNAs, 2 rRNAs and a non-coding control region, which are typical of vertebrate mitogenomes. Phylogenetic analyses of the two species revealed that though both lie within family Cichlidae, they are remotely related.
Keywords: Cichlidae; Mitochondrial DNA; Oreochromis variabilis; Tilapia zilli; Phylogeny